Map from the New York Section of the Society of Woman Geographers (Purdue University Libraries, Archives and Special Collections, 2006)
Map from the New York Section of the Society of Woman Geographers (map shows mermaids and the Arctic Ocean, Atlantic Ocean, Indian Ocean, and Pacific Ocean), undated